Virtual anthropology: a preliminary test of macroscopic observation versus 3D surface scans and computed tomography (CT) scans - Claudine Abegg; Ilaria Balbo; Alejandro Dominguez; Silke Grabherr; Lorenzo Campana; Negahnaz Moghaddam (Oxford University Press, 2021)
Virtual anthropology (VA) is based on applying anthropological methods currently used to analyse bones to 3D models of human remains. While great advances have been made in this endeavour in the past decade, several interrogations concerning how reliable these models are and what their proper use should be remain unanswered. In this research, a fundamental assumption of VA has been investigated: if the way we perceive and apply an anthropological method is truly similar when looking at bones macroscopically and through various 3D media. In order to answer, 10 skulls of known age and sex were scanned using a computed tomography (CT) scanner and a 3D surface scanner. Two observers separately applied a defined staging method to eight suture sites on these skulls, first looking at the bone macroscopically, then at the 3D surface scan, and finally on the CT scan. Two rounds of observation were carried out by each observer. Intra- and inter-observer error were evaluated, and two sample t-tests used to evaluate if the different types of medium used yielded significantly different observations. The results show a high degree of inter-observer error, and that data obtained from 3D surface scans differ from macroscopic observation (confidence level 95%, P ≤ 0.05). CT scans, in these settings, yielded results comparable to those obtained through macroscopic observations. These results offer many possibilities for future research, including indications on the kind of anthropological methods and anatomical landmarks that might be reliably transferable to the virtual environment. All current methods used in traditional anthropology should be tested, and if they prove unreliable, new techniques to analyse bones from virtual models should be developed.Key points Large discrepancies between observation on dry bones and computer-generated 3D models (surface scans or CT scans) could lead to the re-evaluation of the suitability of traditional anthropological methods for application on 3D models. This preliminary study evaluates whether macroscopic, 3D surface scans, and CT scans viewings generate different observations. The results indicate that the data are not always coherent across all three media of observation. Explanations include the aspect given to the bone by the 3D software, differences between handling bones in real life versus on a computer, and level of expertise of the observers.